Institutional arrangements for the new BBNJ agreement: Moving beyond global, regional, and hybrid. (December 2020) - Clark, Nichola A.
Abstract: Negotiators of the BBNJ Agreement face a key challenge: how to structure the agreement such that it achieves meaningful change on-the-water but does not upset the existing constellation of ocean governance regimes. At the heart of this question lies the issue of institutional arrangements, which has come to refer to both the structures and organs that make up the BBNJ Agreement as well as its relative authorities and relationship to other Agreements and organizations. During the Preparatory Committee (PrepCom) phase of the BBNJ discussions, "global", "regional", and "hybrid" emerged as the terms used to describe different models of institutional arrangements. These terms were not universally understood, however, and, in some instances the same term was used by different entities to refer to conflicting ideas. Institutional Arrangements can best be understood as existing on a spectrum, rather than as definitive boxes, defined by an extreme regional model on one end, an extreme global model on the other end, and the hybrid model existing somewhere in the middle. As the BBNJ discussions moved into formal negotiations, there was a movement away from the extreme ends of the spectrum towards some sort of a "hybrid" model. This paper reviews the characteristics and key proponents of each of these different models from the PrepCom phase of the BBNJ discussions and then proposes a framework by which key elements of institutional arrangements can be identified, thus shifting the focus away from the nomenclature of models for institutional arrangements and towards their actual functions.